(untitled) (Al-Academy, 2015)
This paper deals with aesthetic and a sitting position in contemporary Iraqi sculpture and studied this situation, an analytical study to reveal how to employ them in aesthetically pleasing work of art has been research in a sitting position to a lack of technical library for such research, this study includes four chaptersChapter I contains the research problem and its importance in terms of the released address and its objectives in the detection of this situation, how to employ the HDL research is to detect how the aesthetic of the Employment sit position and limits Find business is bronze and stone-dimensional exclusively carried out from 2000 to 2009 AD.Chapter II included the Framework theory and previous studies and with three Investigation Section One Employment aesthetic in the work of art and touched the researcher to some definitions of beauty and harmony in brief The second section was devoted for raw was the title of section the impact of raw material in the implementation of a sitting position in sculpture and researcher dealt with the importance of raw material and its direct impact on the aesthetic of the sculpture and touched researcher ores are the severity of stone and bronze.The third topic addressed About Iraqi contemporary sculpture from 1960 AD to 2010 AD and touched the researcher to a number of contemporary sculptors, Iraqis and some of their carvings, which formed the body and the sitting position.Third situation, action research and how it has been selected sample of the research community, which included eightywere selected in accordance with the work of conscious check, giving the research and the researcher adopted a descriptive analytical method in the analysis of the sample.Chapter IV results WM most important findings of the researcher in employment aesthetic status of sitting through the relations of form and the relationship of the constituent elements of the work and exploitation of the outer space, coupled with the spaces interior lends character aesthetically pleasing to the form of the human sitting as well as the relationship between seating position and shape of the human role in demonstrating aesthetic a sitting position and the degree of this relationship vary from job to another. Some Sculptors work to integrate the full between the seating position and the human form, others work to dispense with seating position completely and focus on the movement of the human form as well as the importance of texture and raw material in making aesthetic to a sitting position.The researcher concluded that the condition of living aesthetics can sculptor employed in the figure by dealing with the curves of sin resulting from the blocks that are concluded also that most of Sculptors tend to form a sitting position of the stone because of its feature training result in durability and strength to accept transport more freely than some other positions